Child Labor in Bolivia and Colombia - Patrinos, Harry Anthony; Grootaert, Christiaan (World Bank, Washington, DC, 2012)
According to the International Labor Organization, 120 million children work full-time worldwide. Virtually all live in poor countries. Legislation has been passed to ban child labor, but it is not enforced or does not address the root causes of the practices such as low income and the opportunity costs of a child's attending school rather than contributing to household income. "A Four-Country Comparative Study of Child Labor" by Christiaan Grootaert and Harry Anthony Patrinos was presented at the Economics of Child Labor Conference in Oslo, in May 2002. The paper was based on a longer study focused on the labor supply decision by the household and identified the key factors affecting child labor, most notably household size and composition, education and employment status of parents, the household's ability to cope with fluctuations on the supply side, and the functioning of the labor market and the prevailing technologies on the demand side.